Total recall (2012) [videorecording (DVD)] - Wiseman, Len; Beckinsale, Kate; Farrell, Colin, 1976-; Nighy, Bill, 1949- (Sony Pictures Home Entertainment, 2012)
Welcome to Rekall, the company that can turn your dreams into real memories. For a factory worker named Douglas Quaid, even though he's got a beautiful wife who he loves, the mind-trip sounds like the perfect vacation from his frustrating life. But when the procedure goes horribly wrong, Quaid becomes a hunted man.